Loadings in Thermal Barrier Coatings of Jet Engine Turbine Blades An Experimental Research and Numerical Modeling - Sadowski, Tomasz; e uthor; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book discusses complex loadings of turbine blades and protective layer Thermal Barrier Coating (TBC), under real working airplane jet conditions. They obey both multi-axial mechanical loading and sudden temperature variation during starting and landing of the airplanes. In particular, two types of blades are analyzed: stationary and rotating, which are widely applied in turbine engines produced by airplane factories.
Keywords: Engineering; Mathematical models; Continuum mechanics; Machinery; Materials science; Engineering; Continuum Mechanics and Mechanics of Materials; Characterization and Evaluation of Materials; Mathematical Modeling and Industrial Mathematics; Machinery and Machine Elements